Modeling and Control of a Pilot Plant Carbon Dioxide Absorption Column for High Carbon Dioxide Content Natural Gas - Ramli, Mohammad Faiz (Universiti Teknologi PETRONAS, 2016)
A dynamic, non-equilibrium model of Monoethanolamine (MEA) absorption column that operate at high operating pressure has been proposed and a study on dynamics behaviour that affect the performance of CO2 absorption process is performed. The MEA solution had been used in this model to absorb CO2 from the natural gas. For the common fact in the oil and gas industry, the high content of CO2 will cause many problem to the operation, thus removing this CO2 from the natural gas itself had become something necessary to ensure smooth operation of the oil and gas industry. Aside from that CO2 gas, other important sour gas exists in the natural gas is H2S. However for this project, the gas that had been study is only CO2 because this is to make sure the project stay within the timeframe given and also to shrink the scope of study as to get more accurate and precise result in the future. To perform a dynamic study, a steady state model needs to be developing first.